2018
DOI: 10.1155/2018/5127917
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Eye Visualizations in the Setting of Hyponatremia

Abstract: Purpose To report a case of closed-eye visualizations and to clarify the different types of hallucinations and their etiologies. Methods Retrospective case report of a patient with closed-eye visualizations secondary to hyponatremia. Clinical findings, physical exam, laboratory assessment, treatment, and disease course from the patient's hospitalization were used in creating this report. Follow-up data after discharge were also obtained. Results Closed-eye visualizations were diagnosed as secondary to hyponatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
(12 reference statements)
1
1
0
Order By: Relevance
“…The closed-eye visual hallucinations reported by our patient are similar to the ones previously described in a few limited cases, distinct from the visual hallucinations described in Charles Bonnet syndrome or psychotic disorders [ 3 - 8 ]. Additional research is required to elucidate the mechanism, etiologies, and clinical implications of this curious phenomenon.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The closed-eye visual hallucinations reported by our patient are similar to the ones previously described in a few limited cases, distinct from the visual hallucinations described in Charles Bonnet syndrome or psychotic disorders [ 3 - 8 ]. Additional research is required to elucidate the mechanism, etiologies, and clinical implications of this curious phenomenon.…”
Section: Discussionsupporting
confidence: 88%
“…Charles Bonnet syndrome is a known condition in which visual hallucinations occur due to visual sensory deprivation caused by vision loss and is most prevalent in elderly patients [ 2 ]. Previously published case reports describe a novel type of visual hallucination occurring primarily with eye closure and are distinct from the visual hallucinations associated with Charles Bonnet syndrome [ 3 - 8 ]. We present a case of closed-eye visual hallucinations with onset before severe alcohol withdrawal.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, gathering a comprehensive medical history is crucial, paying close attention to the nature of the hallucinations, whether they are simple or complex, the specific content involved, any distortion present, any associated triggers, and the patient's insight into their reality. Examining these details allows for a more focused exploration of the potential causes of hallucinations [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypnagogic hallucinations are caused by increased thalamus activation and spontaneous discharges resulting from cortical differentiation [ 10 ]. Peck et al suggested that hyponatremia may increase excitatory influences in the brain, leading to hallucinations [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation